2020
DOI: 10.1038/s41598-020-63677-2
|View full text |Cite
|
Sign up to set email alerts
|

Store-operated Ca2+ entry in primary murine lung fibroblasts is independent of classical transient receptor potential (TRPC) channels and contributes to cell migration

Abstract: Stromal interaction molecules (STIM1, 2) are acting as sensors for Ca 2+ in intracellular stores and activate Orai channels at the plasma membrane for store-operated Ca 2+ entry (SOCE), while classical transient receptor potential (TRPC) channel mediate receptor-operated Ca 2+ entry (Roce). Several reports, however, indicate a role for TRPC in SOCE in certain cell types. Here, we analyzed Ca 2+ influx and cell function in TRPC1/6-deficient (TRPC1/6 −/− ) and STIM1/2-deficient (STIM1/2 ΔpmLf ) primary murine lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…WI-38 fibroblasts also express the transcripts encoding for TRPC1-TRPC6, but the pharmacological sensitivity of histamine-evoked Ca 2+ entry to 10 µM La 3+ and Gd 3+ argues against the involvement of TRPC isoforms. Moreover, a recent investigation demonstrated that TRPC channels do not support SOCE in primary murine lung fibroblasts (Bendiks et al, 2020). Conversely, TRPC channels, which present a single-channel conductance that is 1000-fold larger than Orai3, could be activated by transforming growth factor β and thereby lead to VOC activation via strong membrane depolarization (Mukherjee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WI-38 fibroblasts also express the transcripts encoding for TRPC1-TRPC6, but the pharmacological sensitivity of histamine-evoked Ca 2+ entry to 10 µM La 3+ and Gd 3+ argues against the involvement of TRPC isoforms. Moreover, a recent investigation demonstrated that TRPC channels do not support SOCE in primary murine lung fibroblasts (Bendiks et al, 2020). Conversely, TRPC channels, which present a single-channel conductance that is 1000-fold larger than Orai3, could be activated by transforming growth factor β and thereby lead to VOC activation via strong membrane depolarization (Mukherjee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular Ca 2+ can permeate the plasma membrane through a wide variety of ion channels, including voltage-operated channels (VOC) (Janssen et al, 2015;Rahman et al, 2016) and agonist-operated channels, which comprise three types of channels: 1) receptor-operated channels (ROC) (Saliba et al, 2015), which are ionotropic receptors stimulated by direct ligand binding, 2) second messenger-operated channels (SMOC), which are activated by intracellularly generated mediators, such as cyclic nucleotides, diacylglycerol (Hofmann et al, 2017), and arachidonic acid, and 3) store-operated Ca 2+ channels (SOC), which are the main Ca 2+ entry pathway in non-excitable cells. In the ER, Stromal Interaction Molecules (STIM1/2) act as sensors of ER Ca 2+ concentration that, after a reduction in intraluminal Ca 2+ , multimerize and translocate towards peripheral ER cisternae to functionally interact with the Ca 2+ permeable Orai channels on the plasma membrane (Bendiks et al, 2020). The following influx of Ca 2+ has been termed store-operated Ca 2+ entry (SOCE) and mediates agonist-induced Ca 2+ influx in human fibroblasts isolated from several tissues, including lungs (Guzmán-Silva et al, 2015;Vazquez-de-Lara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of new target proteins mediating this process is therefore an important step toward establishing new biomarkers and future therapeutic options. TRP-channels are expressed and essential for Ca 2+ homeostasis in many cells including fibroblasts (17, 34). We were able to demonstrate an essential role of the classical TRP channel 6 (TRPC6) in murine fibroblast to myofibroblast differentiation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Coverslips were washed with HEPES buffered HBSS and placed under a microscope in a recording chamber with a 500 µl volume. An increase in intracellular Ca 2+ was recorded using a Leica DFC9000 GT camera coupled to an inverted microscope (DMi8, Leica, Wetzlar, Germany) with an 40x/0.85 oil immersions objective at 340 and 380 nm for quantification of [Ca 2+ ] i as described (Bendiks et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%